Safety Assessment of Adjacent Roads Sections via Maximum Entropy Driver’s Perception Field - Nadiia Kulbashna; Iryna Lynnyk; Andrii Galkin; Oleksii Prasolenko; Sergii Dulfan (Communications - Scientific letters of the University of Zilina, 2020)
Characteristics have been developed, by which the boundaries of coherence of adjacent road sections are established in accordance with requirements for the traffic safety. The coordination of adjacent sections of the road is carried out taking into account the driver’s behavior program, which is presented in the work as a value of the maximum entropy of his perception field. The choice of this criterion is determined by the possibility of a comprehensive assessment of many road environment factors that influence the driver. The boundaries of coordination of the maximum entropy values of adjacent road sections with use of the accident rate are established.